AN INVESTIGATION OF THE IMPORTANCE OF BLOG AS LEARNING TOOL FOR WRITING - Artikasari, Novi; Salam, Urai; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research aimed to investigate fourth semester students’ experiences in using blog as learning tool for writing. The method of this research was case study. The subjects of this research were five students of fourth semester of English Language Education Study Program of FKIP Untan Pontianak in Academic Year 2013/2014.The data of this research were obtained from the observation and interview. The findings indicated that every student affirmed that blog carried several benefits in supporting their learning especially in writing because blog has a program that can correct their mistakes automatically in writing and the students can practice their writing skill. As the result, blog improved students’ writing skill in term of vocabulary, grammar, ideas, and the process of writing itself. Besides that, through writing in blog students canlearn to be more cooperative and they can build communication with people around the world. Moreover, knowledge and ideas that students shared on their blogs were still acessible. Key words: Blog, Students’ Experiences, Writing Abstrak: Penelitian ini bertujuan untuk menginvestigasi pengalaman mahasiswa semester empat dalam menggunakan blog sebagai media untuk menulis. Dalam penelitian ini penulis menggunakan metode studi kasus. Subjek dari penelitian ini adalah mahasiswa semester empat program studi Bahasa Inggris di FKIP Untan Pontianak tahun ajaran 2013/2014. Data dikumpulkan melalui observasi dan interview. Hasil penelitian menunjukkan bahwa setiap mahasiswa menyatakan bahwa blog memberikan beberapa manfaat dalam mendukung belajar mereka khususnya dalam menulis karena blog memiliki program yang bisa mengoreksi secara otomatis kesalahan mereka dalam menulis dan mereka bisa mempraktikkan kemampuan menulis mereka. Hasilnya, blog dapat memperbaiki kemampuan menulis mahasiswa khususnya dalam kosa kata, tatabahasa, ide, dan proses dalam menulis tersebut. Selain itu, melalui menulis dalam blog mahasiswa bisa belajar lebih cooperative serta mereka bisa membangun komunikasi dengan orang-orang di seluruh dunia. Lagipula, pengetahuan dan ide-ide yang mereka bagikan dalam blog mereka masih bisa diakses oleh pembaca.   Kata kunci: Blog, Pengalamanmahasiswa, Menulis